Pollen from Arabidopsis thaliana and other Brassicaceae are functionally omniaperturate. Issue 6 (22nd June 2016) - Edlund, Anna F.; Zheng, Qin; Lowe, Nancy; Kuseryk, Skye; Ainsworth, Krystle L.; Lyles, Robert H.; Sibener, Steven J.; Preuss, Daphne
Abstract : PREMISE OF THE STUDY: Most pollen walls are interrupted by apertures, thin areas providing access to stigmatic fluids and exit points for pollen tubes. Unexpectedly, pollen tubes of Arabidopsis thaliana are not obligated to pass through apertures and can instead take the shortest route into the stigma, passing directly through a nonaperturate wall. METHODS: We used stains and confocal microscopy to follow early pollen tube formation in A. thaliana and 200+ other species. We germinated pollen in vitro and in situ (at control and high humidities) and also used atomic force microscopy to assay material properties of nonaperture and aperture walls. KEY RESULTS: Pollen tubes of A. thaliana breached nonaperture walls despite these being an order of magnitude stiffer than aperture walls. Breakout was associated with localized swelling of the pectin‐rich (alcian blue positive) intine. The precision of pollen tube exit at the pollen–stigma interface was lost at high humidity. Pollen from ∼4% of the species surveyed exhibited breakout germination behavior; all nine breakout species identified so far are in the Brassicaceae family (∼25% of the Brassicaceae sampled) and are scattered across seven tribes. CONCLUSIONS: The polarity of pollen germination in A. thaliana is externally induced, not linked to aperture location. The biomechanical force for breaking nonaperture walls is found in localized swelling of intine pectins. As such, the pollen from A. thaliana, and likely many Brassicaceae family members, are functionally omniaperturate. This new mechanism for germination between extant apertures raises questions about exine porosity and the diversity of mechanisms across taxa.